2020
DOI: 10.1021/acs.langmuir.9b03923
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Activity of an Osmotically Stressed Liposome in a Finite Hypotonic Environment

Abstract: A lipid vesicle, or simply called a liposome, represents a synthetic compartment for the examination of transmembrane transport and signaling phenomena. Yet, a liposome is always subjected to size and shape fluctuations due to local and global imbalance of internal and external osmotic pressures. Here, we show that an osmotically stressed liposome placed within a hypotonic spherical bath undergoes cyclic dynamics described by a periodic sequence of swelling and relaxation phases. These two phases are interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…However, when water moves to the lumen, under the action of osmotic forces, the membrane structure cannot preserve its initial shape (the vacuole is transformed into a sphere) and then even its integrity. For instance, when artificial vacuoles are made in hypertonic solution, and then placed into hypotonic solution, water molecules begin to move into the lumen, causing transient lytic membrane holes, and fluid starts to go out of the vacuole [ 24 ]. The enrichment of lipids, which is able to induce membrane curvature in the rims of Golgi cisternae, cannot counteract other membrane forces [ 2 ].…”
Section: Factors Determining the Membrane Curvaturementioning
confidence: 99%
“…However, when water moves to the lumen, under the action of osmotic forces, the membrane structure cannot preserve its initial shape (the vacuole is transformed into a sphere) and then even its integrity. For instance, when artificial vacuoles are made in hypertonic solution, and then placed into hypotonic solution, water molecules begin to move into the lumen, causing transient lytic membrane holes, and fluid starts to go out of the vacuole [ 24 ]. The enrichment of lipids, which is able to induce membrane curvature in the rims of Golgi cisternae, cannot counteract other membrane forces [ 2 ].…”
Section: Factors Determining the Membrane Curvaturementioning
confidence: 99%
“…Moreover, while the sizes remained similar over time for the two formulations diluted in 5% glucose, the liposomal AmB 4 mg/mL suspension showed an increase in the diameter from 87 nm to 104 nm. This increase in diameter could be related to the external osmotic pressure to which the liposomes are subjected, being dispersed in a hypotonic medium (sterile water) [ 26 ]. Regarding the superficial electric charge measured by DLS, we found that the zeta potential hardly changed with time within 4 days or 1 week ( Table 2 , Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Transient pore formation followed by pulsating swell-burst-cycles is a commonly observed phenomenon of vesicles exposed to hypotonic conditions. 40,41 Thus, the transient uptake profiles reflect loss of betaine after the vesicles reach a critical stress point (Figure 3G). A detailed description of the loss of betaine is given in Figure SI-6.…”
Section: Metabolic Control Of Reactions Inside the Energy-consuming V...mentioning
confidence: 98%